Teacher Strategies in Organizing Innovative Classrooms at MI Maraqitta'limat Sidutan Kayangan Academic Year 2024/2025 - Jannah, Rauhun (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research aims to analyze the strategies implemented by teachers in organizing innovative classrooms at MI Maraqitta'limat Sidutan Kayangan during the 2024/2025 school year. Good classroom settings can have a positive impact on the quality of learning, create a pleasant learning atmosphere, and increase student motivation and creativity. This research uses a qualitative approach with a case study design. Data was collected through direct observation in the classroom, interviews with several teachers, and analysis of documents related to classroom settings. The research results show that teachers at MI Maraqitta'limat Sidutan Kayangan implement several innovative strategies, such as flexible seating arrangements to support various learning activities, the use of interesting and varied learning media, and the creation of a comfortable classroom environment that supports student creativity. Despite facing challenges such as limited budgets and limited space, teachers try to maximize the potential of classrooms to support more effective learning. Based on these findings, it can be concluded that innovative classroom arrangements have a very important role in improving the quality of learning and creating an active and enjoyable learning environment for students